Gestión operativa y su impacto en la calidad de los servicios públicos del registro de la propiedad del Cantón Valencia, año 2023 - Chalar Suarez, Juana Patricia (2025)
This research aims to evaluate the impact of operational management on the quality of public services of the Property Registry of the Canton of Valencia. The research addressed the issue from a mixed approach, combining qualitative and quantitative methodologies, allowing for a comprehensive view of the current state of operational management. It comprised three differentiated phases: first, through the technique of direct observation, the organizational structure of the institution, the available technological equipment, as well as the operational procedures carried out within the institution were analyzed, which allowed the identification of significant aspects that influence the internal management of the Property Registry; the second phase of the research included an interview with the department head, which provided detailed information on the influence of staff training, offering an administrative perspective on management and the processes implemented to improve services, while at the same time, the focus group with operational staff allowed for the analysis of internal dynamics and their impact on overall results; finally, in the third phase, the survey directed to external users offered essential data regarding their experience, satisfaction, and the critical areas to be considered in improving the service. The results obtained from this research allow the identification of the main shortcomings in operational processes and in the quality of service provided to citizens. It was observed that staff, at times, show a lack of empathy in dealing with users, and that the organizational structure is not adequate to ensure institutional operational efficiency; furthermore, it was evidenced that digitalization efforts have not been entirely effective. Therefore, the need to implement improvements in procedures is emphasized to enhance the delivery of public services with greater efficiency and effectiveness.